A aceitação do utilizador face aos diferentes formatos de anúncios - Ferreira, Hugo Daniel Gomes (2021)
Digital campaigns are now a major trend in digital marketing, moreover with the emergence of the covid-19 pandemic, it has become a habit to invest on sponsored publications in order to reach a bigger number of consumers and develop brand awareness among them. As interest grew of users connected daily to the digital world, it become clear to provide digital channels with platforms that allow the purchase of goods and products without having to leave home. That way, the main purpose of this research is to provide an overview, from the perspective of users and how they were impacted by the different formats of digital advertisements. We chose to use a quantitative method, where a survey was carried out among users of social networks and the internet. The conclusions obtained makes us conclude that the ads in image and when well segmented assume a special importance in the acceptance of digital campaigns and in the consequent conversion according to the stipulated objective. What it was possible to reach through this study assumes a special importance for digital marketing professionals and campaign managers. Furthermore, the study proves the importance and potential that segmentation has in digital marketing planning and strategy. We can therefore assume, despite the different and varied ad formats existing in different digital channels, the image format associated with segmentation makes acceptance much more effective on social networks. On the other hand, search engines favor the understanding and feasibility of the address.